Discovering the 1858 Lava Flow Field at Somma-Vesuvius (Italy) Through geoitinerary, Virtual Tour and 3D Reconstruction of Volcanic Landforms - Thomas Lemaire; Daniele Morgavi; Paola Petrosino; Sonia Calvari; Leopoldo Repola; Diego Di Martire; Ettore Valente (Geoheritage, 2026)
Geotourism in volcanic areas attracts millions of visitors each year travelling to see and explore volcanic areas. One of the world’s most famous and visited volcanic areas is Somma-Vesuvius. Here, tourism is mainly concentrated around the central crater while the rest of the volcano, part of Vesuvius National Park, is largely unvisited. The volcano’s worldwide fame is primarily linked to its explosive activity, most notably the famous eruption that destroyed Pompeii and Herculaneum in 79 CE. Yet Somma-Vesuvius underwent long periods of effusive activity, such as the 1631–1944 eruptive cycle. On the volcano, there are examples of archetypal lava flows, including the 1858 flow field in which lava tubes formed. We propose a geoitinerary through the 1858 lava flow field that includes five sites, three lava tubes, an ephemeral vent and a tumulus, that allows people to evidence effusive activity and discover volcanic features formed during such activity at Somma-Vesuvius. A website was developed to host a virtual tour, which includes 360° images and an explicative panel for each site. The largest lava tube was 3D scanned to reconstruct its geometry, and to conserve a virtual copy of this fragile structure. Both the website and 3D scan aim to sensibilize people either not used to hiking or with physical impediment about volcanic landforms and their scientific relevance. The pertinence of the geoitinerary has been assessed by a SWOT analysis. The geoitinerary may contribute to divert tourist traffic away from the volcanic cone, while raising awareness on volcanic processes.

Emplacement and growth of a stacked tube-fed lava flow field: the 2021 Tajogaite eruption (La Palma, Canary Islands, Spain) - Sonia Calvari; Gaetana Ganci; Inés Galindo; David Sanz-Mangas; Daniele Morgavi; Octavio Fernandez Lorenzo (Bulletin of Volcanology, 2025)
On 19 September 2021, the Cumbre Vieja volcano in the southern part of La Palma (Canary Islands) erupted after 50 years of quiescence. A northwest-southeast eruptive fissure opened on the west flank of the volcano, producing explosive and effusive activity that lasted until 13 December 2021. The explosive activity from the fissure built up a new cone named Tajogaite, and the discharge of high temperature and low viscosity magma gave rise to lava flows. These spread from the base of the cone to the west, reaching the sea and forming a complex lava flow field with the stacking of flows and lava tube pathways. The eruption caused the destruction of 2988 buildings and ~ 12 km 2 of urbanized areas, farmland, and plantations, emplacing ~ 200 × 10 6 m 3 lava and ~ 45 × 10 6 m 3 tephra, with ~ 5 × 10 6 m 3 lava forming a lava delta. This eruption offered a unique opportunity to study the emplacement of a complex lava tube network developed initially within ‘a‘ā arterial flows and later on within pāhoehoe flows. We present an account of the expansion of the lava flow field and of the development of lava tubes gathered from satellite images and field surveys. We go on to characterize the processes of lava flow field development and lava tube formation and growth and estimate the time-averaged discharge rate and erupted lava volume. From the start of the eruption to the end of October, the lava flow field was mainly characterized by the emplacement of four sequential ‘a‘ā arterial flows. Along these flows, master lava tubes rapidly developed by the roofing-over of lava channels within a few days from their emplacement. The ‘a‘ā arterial flows advanced in a caterpillar-like fashion, alternating proximal lava channel overflows and drainage corresponding to the slowing down and accelerating of the lava front. From November to the end of the eruption, a decreased discharge rate resulted in the output of mainly pāhoehoe flows emplaced in the medial portion of the lava flow field. Overlapping ‘a‘ā and pāhoehoe flow units formed stacked tube systems. Our results highlight the speed and processes of lava flow field development and lava tube growth during an effusive eruption on a steep slope (> 4°), the complexity of lava tubes at multiple levels in a stacked flow sequence, and provide useful information for hazard mitigation should a new eruption occur in this area or on other steep volcanoes.

Very fast canyon formation and evolution along active volcanic flanks: A case from Stromboli Island - Daniele Casalbore; Federico Di Traglia; Massimiliano Favalli; Alessandro Fornaciai; Claudia Romagnoli; Riccardo Civico; Tullio Ricci; Paolo Berardino; Lorenzo Borselli; Pierfrancesco Calabria; Sonia Calvari; Tommaso Carlà; et al. (Geomorphology, 2025)

Lava flow field development and lava tube formation during the 1858–1861 eruption of Vesuvius (Italy), unravelled by historical documentation, lidar data and 3D mapping - Thomas Lemaire; Daniele Morgavi; Paola Petrosino; Sonia Calvari; Leopoldo Repola; Lorenzo Esposito; Diego Di Martire; Vincenzo Morra; Francesco Frondini (Journal of Volcanology and Geothermal Research, 2024)

Search for anomalies in Stromboli's pre-paroxysm activity through an automatic hybrid method of time series analysis - Fabrizio Ambrosino; Carlo Sabbarese; Giovanni Macedonio; Walter De Cesare; Antonietta M. Esposito; Federico Di Traglia; Nicola Casagli; Teresa Nolesini; Salvatore Inguaggiato; Fabio Vita; Sonia Calvari; Giuseppe Salerno; et al. (Journal of Volcanology and Geothermal Research, 2024)

Correction to: Generation of deposit-derived pyroclastic density currents by repeated crater rim failures at Stromboli Volcano (Italy) - Federico Di Traglia; Paolo Berardino; Lorenzo Borselli; Pierfrancesco Calabria; Sonia Calvari; Daniele Casalbore; Nicola Casagli; Francesco Casu; Francesco Latino Chiocci; Riccardo Civico; Walter De Cesare; Claudio De Luca; et al. (Bulletin of Volcanology, 2024)

Generation of deposit-derived pyroclastic density currents by repeated crater rim failures at Stromboli Volcano (Italy) - Federico Di Traglia; Paolo Berardino; Lorenzo Borselli; Pierfrancesco Calabria; Sonia Calvari; Daniele Casalbore; Nicola Casagli; Francesco Casu; Francesco Latino Chiocci; Riccardo Civico; Walter De Cesare; Claudio De Luca; et al. (Bulletin of Volcanology, 2024)
The gravitational instability of hot material deposited during eruptive activity can lead to the formation of glowing avalanches, commonly known as deposit-derived pyroclastic density currents (PDCs). These currents can travel hundreds of metres to several kilometres from the source at exceptionally high temperatures, posing a catastrophic hazard to areas surrounding steep-slope volcanoes. The occurrence of deposit-derived PDCs is often associated with crater rim failure, which can be triggered by various factors such as magma thrust from dike injection, magma fingering, bulging or less commonly, powerful explosions. Here, the in-depth study of data from the multi-parametric monitoring network operating on Stromboli (Italy), including video surveillance, seismicity and ground deformation data, complemented by remote topographic sensing data, has facilitated the understanding of the events leading to the crater rim collapse on 9 October and 4 December 2022. The failures resulted in the remobilisation of 6.4 ± 1.0 × 10 3 m 3 and 88.9 ± 26.7 × 10 3 m 3 of material for the 9 October and the 4 December 2022, respectively, which propagated as PDCs along the NW side of the volcano and reached the sea in a few tens of seconds. These events were characterised by a preparatory phase marked by an increase in magmatic pressure in the preceding weeks, which correlated with an increase in the displacement rate of the volcano’s summit. There was also an escalation in explosive degassing, evidenced by spattering accompanied by seismic tremors in the hours before the collapse. These events have been interpreted as an initial increase in magma vesicularity, followed by the release of gas once percolation threshold was reached. The degassing process induced densification of the magma, resulting in increased thrust on the conduit walls due to increased magmastatic pressure. This phase coincided with crater rim collapse, often followed or accompanied by the onset of lava overflow phases. A mechanism similar to the one proposed may shed light on similar phenomena observed at other volcanoes. The analysis performed in this study highlights the need for a multi-parametric and multi-platform approach to fully understand such complex phenomena. By integrating different data sources, including seismic, deformation and remote sensing data, it is possible to identify the phenomena associated with the different phases leading to crater rim collapse and the subsequent development of deposit-derived PDCs.

When the lava meets the sea: emplacement of the 2–4 ka San Bartolo lava flow field, Stromboli volcano (Italy) - Rasia Shajahan; Andrew J. L. Harris; Elena Zanella; Lucia Gurioli; Claudio Robustelli Test; Sonia Calvari; Lodovico Drovanti (Bulletin of Volcanology, 2024)
When a lava flow enters a body of water, either a lake, sea, river or ocean, explosive interaction may arise. However, when it is an 'a'ā lava flow entering water, a more complex interaction occurs, that is very poorly described and documented in literature. In this paper, we analysed the 2–4 ka San Bartolo lava flow field emplaced on the north flank of Stromboli volcano, Italy. The lava flow field extends from ~ 650 m a.s.l. where the eruptive fissure is located, with two lava channels being apparent on the steep down to the coast. Along the coast the lava flow field expands to form a lava delta ~ 1 km wide characterised by 16 lava ‘Flow’ units. We performed a field survey to characterise the features of lava entering the sea and the associated formation of different components and magnetic measurements to infer the flow fabrics and emplacement process of the lava flow system. We measured the density, porosity and connectivity of several specimens to analyse the effect of lava-water interaction on the content in vesicles and their connectivity and conducted a macroscopic componentry analysis (clast count) at selected sites to infer the character of the eroded offshore segment of the lava flow field and its component flow units. The collected data allowed us to define the main components of a lava delta fed by 'a'ā lava flows, with its channels, littoral units, ramps, lava tubes, and inflated pāhoehoe flows controlled by the arterial 'a'ā flow fronts. The spatial organisation of these components allowed us to build a three-step descriptive model for 'a'ā entering a water. The initial stage corresponds to the entry of channel-fed 'a'ā lava flow into the sea which fragments to form metric blocks of 'a'ā lava. Continued lava supply to the foreshore causes flow units to stall while spreading over this substrate. Subsequent 'a'ā lava flow units ramp up behind the stalled flow front barrier. Lava tubes extending through the stalled flow barrier feed the seaward extension of a bench made of several pāhoehoe flow units.

UAV-based remote sensing surveys of lava flow fields: a case study from Etna’s 1974 channel-fed lava flows - Massimiliano Favalli; Alessandro Fornaciai; Luca Nannipieri; Andrew Harris; Sonia Calvari; Charline Lormand (Bulletin of Volcanology, 2018)

Translations of volcanological terms: cross-cultural standards for teaching, communication, and reporting - Andrew J. L. Harris; Alexander Belousov; Sonia Calvari; Hugo Delgado-Granados; Matthias Hort; Ken Koga; Estuning Tyas Wulan Mei; Agung Harijoko; José Pacheco; Jean-Marie Prival; Carmen Solana; Þorvaldur Þórðarson; et al. (Bulletin of Volcanology, 2017)

Monitoring crater-wall collapse at active volcanoes: a study of the 12 January 2013 event at Stromboli - Sonia Calvari; Emanuele Intrieri; Federico Di Traglia; Alessandro Bonaccorso; Nicola Casagli; Antonio Cristaldi (Bulletin of Volcanology, 2016)

Erratum to: Lava discharge during Etna’s January 2011 fire fountain tracked using MSG-SEVIRI - Mathieu Gouhier; Andrew Harris; Sonia Calvari; Philippe Labazuy; Yannick Guéhenneux; Franck Donnadieu; Sébastien Valade (Bulletin of Volcanology, 2012)

Lava discharge during Etna's January 2011 fire fountain tracked using MSG-SEVIRI - Mathieu Gouhier; Andrew Harris; Sonia Calvari; Philippe Labazuy; Yannick Guéhenneux; Franck Donnadieu; Sébastien Valade (Bulletin of Volcanology, 2012)

The Miocene Costa Giardini diatreme, Iblean Mountains, southern Italy: model for maar-diatreme formation on a submerged carbonate platform - Sonia Calvari; Lawrence H. Tanner (Bulletin of Volcanology, 2011)

Reconstruction of the eruptive activity on the NE sector of Stromboli volcano: timing of flank eruptions since 15 ka - Sonia Calvari; Stefano Branca; Rosa Anna Corsaro; Emanuela De Beni; Lucia Miraglia; Gianluca Norini; Jan Wijbrans; Enzo Boschi (Bulletin of Volcanology, 2011)

Lava effusion rate definition and measurement: a review - Andrew J. L. Harris; Jonathan Dehn; Sonia Calvari (Bulletin of Volcanology, 2007)

Strombolian explosive styles and source conditions: insights from thermal (FLIR) video - Matthew R. Patrick; Andrew J. L. Harris; Maurizio Ripepe; Jonathan Dehn; David A. Rothery; Sonia Calvari (Bulletin of Volcanology, 2007)

The changing morphology of an open lava channel on Mt. Etna - John E. Bailey; Andrew J. L. Harris; Jonathan Dehn; Sonia Calvari; Scott K. Rowland (Bulletin of Volcanology, 2006)

Lava effusion rates from hand-held thermal infrared imagery: an example from the June 2003 effusive activity at Stromboli - Andrew Harris; Jon Dehn; Matt Patrick; Sonia Calvari; Maurizio Ripepe; Luigi Lodato (Bulletin of Volcanology, 2005)

A multi-disciplinary study of the 2002?03 Etna eruption: insights into a complex plumbing system - Daniele Andronico; Stefano Branca; Sonia Calvari; Michael Burton; Tommaso Caltabiano; Rosa Anna Corsaro; Paola Del Carlo; Gaetano Garf; Luigi Lodato; Lusia Miraglia; Filippo Mur; Marco Neri; et al. (Bulletin of Volcanology, 2005)

Instabilities in the summit region of Mount Etna during the 1999 eruption - Sonia Calvari; Harry Pinkerton (Bulletin of Volcanology, 2002)